SYSTEMATIC LITERATURE REVIEW: ANALISIS IMPLEMENTASI KURIKULUM DI SD - Marlina; Rahma Ashari Hamzah; Siti Ayudiah Alim; Nur Hasirah (Jurnal Pendidikan Pemuda Nusantara, 2026)
The implementation of the curriculum at the elementary school level (SD) holds a very high urgency in creating a learning ecosystem that is applicable, effective, and able to adapt to the dynamics of the times as well as the unique characteristics of students. This research was conducted to dissect in depth the process of curriculum implementation in elementary schools by adopting the “Systematic Literature Review”(SLR) method. Methodologically, this study applies a quantitative approach that relies on literature studies as the main instrument for data collection. Researchers collected 30 credible references consisting of 25 scientific journal articles and 5 book literature with a publication range between 2020 and 2025. The search process focused on relevant Indonesian-language scientific works, then strictly curated through the stages of identification, filtration, and feasibility testing until leaving 9 core articles for further analysis. The research findings show that the effectiveness of curriculum implementation is greatly influenced by the level of teacher competence, student mental readiness, the availability of supporting facilities, and the direction of internal school policies. In addition, flexible and student-centered learning models have been proven to be able to significantly boost the quality of education. However, real challenges such as limited operational resources and a lack of intensive training for educators are still frequently encountered in the field. Therefore, collective synergy from all stakeholders is needed to strengthen the quality of curriculum implementation so that national education goals can be realized more optimally and sustainably going forward.